Energy and greenhouse effect emission analysis in small-scale rice cultivation: a case study in Tulungagung, Indonesia - Lutfi, Musthofa; Astuti, Nining Pambudi; Ahmad, Ary Mustofa; Mustaniroh, Siti Asmaul; Luqman, Asaduddin; Mindarti, Lely Indah (Frontiers in Energy Research, 2025)
Small-scale rice farming plays a vital role in Indonesia’s food security but presents considerable environmental challenges due to inefficient energy use and high greenhouse gas (GHG) emissions. This study investigates energy inputs and GHG emissions in smallholder rice farms in Tulungagung, East Java, to identify inefficiencies and recommend sustainable interventions. Data were collected from 16 farms across four subdistricts during the second planting season using structured surveys. Energy inputs—derived from fertilizers, machinery, fuel, and labor—were quantified using standardized coefficients, while GHG emissions were estimated based on the use of fertilizers, pesticides, and fuel. The results showed that fertilizers, particularly nitrogen-based ones, accounted for 96.6% of total energy inputs (18,270.96 MJ/ha). Average GHG emissions reached 21,431.6 kg CO2-eq/ha, with significant contributions from pesticides (31.8%) and fertilizers. Additional emissions stemmed from methane in flooded fields and nitrous oxide from fertilizer overuse. The system exhibited low energy efficiency (0.61%) and high specific energy consumption (127 MJ/kg), indicating substantial inefficiencies. These findings underscore the need for integrated nutrient management, site-specific mechanization, and renewable energy adoption to enhance the environmental sustainability of rice farming. Future studies should focus on the implementation of precision agriculture and biofertilizers to mitigate environmental impacts while improving productivity.